2022
DOI: 10.21203/rs.3.rs-1926149/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N6-methyladenosine-mediated SH3BP5-AS1 upregulation promotes GEM chemoresistance in pancreatic cancer by activating the Wnt signaling pathway

Abstract: Background: Pancreatic cancer (PC) is highly malignant. Chemotherapy is the main treatment strategy, especially for patients with advanced PC. However, chemoresistance has always been a frequently encountered bottleneck. Hence, there is an urgent need to enhance the sensitivity of PC to gemcitabine (GEM).Results: We demonstrated that SH3BP5-AS1 was significantly upregulated in GEM-resistant PC and predicted a poorer prognosis. SH3BP5-AS1 stability was regulated by ALKBH5/IGF2BP1-mediated m6A modification. Loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…FTO is associated with various signaling pathways, for example, PKA/CREB (Hu et al, 2022), TNF-α (Li et al, 2022b), ERK (Xiao et al, 2022b), WNT (Kim et al, 2022) and JAK2/ STAT3 pathways (Shen et al, 2021). ALKBH5 is involved in many signaling pathways, including WNT (Lin et al, 2022), PTEN/AKT (He et al, 2021), NF-κB (Qu et al, 2022), AKT (Wang et al, 2020). Interestingly, many studies have shown that H. pylori infection is closely related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…FTO is associated with various signaling pathways, for example, PKA/CREB (Hu et al, 2022), TNF-α (Li et al, 2022b), ERK (Xiao et al, 2022b), WNT (Kim et al, 2022) and JAK2/ STAT3 pathways (Shen et al, 2021). ALKBH5 is involved in many signaling pathways, including WNT (Lin et al, 2022), PTEN/AKT (He et al, 2021), NF-κB (Qu et al, 2022), AKT (Wang et al, 2020). Interestingly, many studies have shown that H. pylori infection is closely related to these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%